1994
DOI: 10.1021/bi00173a026
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Restriction Endonuclease EcoRV with the Deoxyguanosine and Deoxycytidine Bases in Its Recognition Sequence

Abstract: The interaction of the EcoRV restriction endonuclease with the dG and dC bases in its recognition sequence (GATATC) has been studied using base analogues. These modified dG and dC bases each have a single potential protein contact removed. The analogues have been incorporated into the self-complementary dodecamer d(pGACGATATCGTC) at the appropriate positions (underlined). Many of the analogues caused no change in the Tm of the duplex or else lowered the Tm by a small amount such that a duplex was still formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 47 publications
(93 reference statements)
3
23
1
Order By: Relevance
“…In the cognate complex, the protein makes extensive hydrogen-bonding contacts with the bases in the DNA major groove; these contacts are absent in the non-cognate complex and the corresponding protein elements are largely disordered. The observed protein-base contacts are generally consistent with those inferred from biochemical studies on the effects of modi®ed DNA bases (Mazzarelli et al, 1989;Newman et al 1990b;Waters & Connolly, 1994). In summary, the cognate complex in the absence of Mg 2 appears to have all the structural properties expected for a speci®c recognition complex, but the non-cognate complex does not.…”
Section: Introductionsupporting
confidence: 77%
“…In the cognate complex, the protein makes extensive hydrogen-bonding contacts with the bases in the DNA major groove; these contacts are absent in the non-cognate complex and the corresponding protein elements are largely disordered. The observed protein-base contacts are generally consistent with those inferred from biochemical studies on the effects of modi®ed DNA bases (Mazzarelli et al, 1989;Newman et al 1990b;Waters & Connolly, 1994). In summary, the cognate complex in the absence of Mg 2 appears to have all the structural properties expected for a speci®c recognition complex, but the non-cognate complex does not.…”
Section: Introductionsupporting
confidence: 77%
“…Restriction enzymes were purchased from NBL (Northumbria Biological Laboratories, Cramlington, UK) and Taq DNA polymerase was from Boehringer Mannheim (Lewes, UK). Oligonucleotides primers for PCR amplification were synthesized on an Applied Biosystems 381A DNA synthesizer using the phosphoramidite method (Newman et al, 1990;Connolly 1991Connolly , 1992Waters and Connolly, 1994) with reagents from either Cruachem (Glasgow, Scotland) or Applied Biosystems (Warrington, UK). The phosphoramidite of 6-methyldeoxyadenosine was purchased from Pharmacia.…”
Section: Methodsmentioning
confidence: 99%
“…The similarity of the two rate constants is in agreement with the assertion that the trajectories comprise molecular events like DNA bending, DNA hydrolysis, and product release, but not DNA binding, which is expected to be much slower in case of the 30-bp spacer because of steric hindrance. The catalytic cycle of EcoRV with short (7-14 bp) substrate DNAs has been investigated in bulk by using FRET, stopped-flow fluorescence, fluorescence anisotropy, and quench-flow methods (46,48,49). These studies found that the turnover rate k cat is limited by rates of DNA hydrolysis and product release (Fig.…”
Section: Dynamics Of Ecorv-catalyzed Dna Cleavage As Measured With Plmentioning
confidence: 99%